Rural Health Status and Health Care in Bihar: A Case Study - Yadav, Abhinav Singh; Tewari, Vayu; Cheepi, Pulliah (Journal of Neonatal Surgery, 2025)
The population of rural areas face distinct health challenges due to economic conditions, cultural/behavioural factors, and health provider shortages that combine to impose striking disparities in health outcomes among them. Physician shortages persist in many rural communities and the proportion of rural hospitals under financial stress is much higher than urban hospitals. The healthcare situation in select rural areas is unfavourably compared to the rest of the country. Government policies have attempted to address some of these inequalities by encouraging network development and awareness. Public health infrastructure in rural Bihar is not well understood, but it is potentially the most fragile aspect of the rural healthcare continuum. Investing in health not only improves the performance of individuals but also supports long-run growth and prosperity. In rural Bihar, government health infrastructure and facilities are not appropriate for meeting these challenges. Rohtas district has a population of 2.96 million of which 85.54% resides in rural areas. A major priority of health service providers has been to improve the health of ‘disadvantaged’ rural communities, particularly the rural poor, infants, women, children and the disabled. The Ministry of Health and Family Welfare is the main healthcare provider for rural communities, with general practitioners also playing a supporting role. By using primary data and regression analysis from a case study conducted in Rohtas district, evaluate the role of socio-economic variables, particularly income, literacy and healthcare infrastructure, in shaping health expenditure behaviour among households. The study recommends that addressing Bihar’s rural inequalities cannot be possible only through financial assistance, rather a holistic policy is needed, which addresses educational awareness, healthcare infrastructure and economic support mechanisms.